3-Dimensional target coverage assessment for MRI guided esophageal cancer radiotherapy. (June 2020) - Boekhoff, M.R.; Defize, I.L.; Borggreve, A.S.; Takahashi, N.; van Lier, A.L.H.M.W.; Ruurda, J.P.; van Hillegersberg, R.; Lagendijk, J.J.W.; Mook, S.; Meijer, G.J.
Highlights: Online MR-guided soft-tissue registration protocols exhibited modest improvements of the geometric target coverage probability as compared to online CBCT-guided bone match protocols. Therefore, highly conformal target irradiation using online MR-guidance can only be achieved by implementing on-table adaptive workflows where new treatment plans are daily generated based on the anatomy of the day. Abstract: Purpose: This study aimed to quantify the coverage probability for esophageal cancer radiotherapy as a function of a preset margin for online MR-guided and (CB)CT-guided radiotherapy. Methods: Thirty esophageal cancer patients underwent six T2-weighted MRI scans, 1 prior to treatment and 5 during neoadjuvant chemoradiotherapy at weekly intervals. Gross tumor volume (GTV) and clinical target volume (CTV) were delineated on each individual scan. Follow-up scans were rigidly aligned to the bony anatomy and to the clinical target volume itself, mimicking two online set-up correction strategies: a conventional CBCT-guided set-up and a MR-guided set-up, respectively. Geometric coverage probability of the propagated CTVs was assessed for both set-up strategies by expanding the reference CTV with an isotropic margin varying from 0 mm to 15 mm with an increment of 1 mm. Results: A margin of 10 mm could resolve the interfractional changes for 118 out of the 132 (89%) analyzed fractions when applying a bone-match registration, whereas the CTV was adequately covered in 123 (93%) fractions when the registration was directly performed at the CTV itself (soft-tissue registration). Closer analyses revealed that target coverage violation predominantly occurred for distal tumors near the junction and into the cardia. Conclusion: Online MR-guided soft-tissue registration protocols exhibited modest improvements of the geometric target coverage probability as compared to online CBCT-guided bone match protocols. Therefore, highly conformal target irradiation using online MR-guidance can only be achieved by implementing on-table adaptive workflows where new treatment plans are daily generated based on the anatomy of the day.